Characterization of Eggshells Nanocatalyst: Synthesized by Bottom-Up Technology - Jeremiah Odhek Masime; Erich Okoth Ogur; Betty N. Mbatia; Austin Ochieng' Aluoch; Geoffrey Otieno (Walisongo Journal of Chemistry, 2022)
The sol-gel technique was used to prepare the nanocatalyst from waste egg shells for the production of yellow oleander biodiesel. In this study, the physicochemical and catalytic properties of the nanocatalysts were investigated using: X-ray fluorescence spectrometry (XRF), transmission electron microscopy (TEM), the Barrett-Joyner-Halenda (BJH) model to quantify the pore structure of the samples, and Brunauer-Emmett-Teller (BET) to calculate the exact surface area were the techniques used. The results of the EDX, and XRF analysis showed that the synthesized nanocatalyst was majorly CaO. At 90.46 ± 1.73%, this was higher than the control for incinerated eggshells. From TEM images the particles were spherical in shape with particle sizes ranging from ≈ 7 to 41 nm. BET analysis results indicated that the nanocatalyst was mesoporous with surface area, average pore diameter, and pore volume was; 5.54 ± 0.48 m2/g, 18.57 ± 2.16 nm, and ≈ 0.016 ± 0.0 – 0.017 ± 0.0 cm³/g, respectively. The surface area to volume ratios were 3.27 ± 108 m-1, 2.52 ± 108, and 1.95 ± 108 m-1, respectively. Incinerated eggshells highest followed the synthesized nanocatalyst and CaO, respectively. The synthesized eggshell nanocatalyst was found to be a potential nanocatalyst.